Estudo da hidrólise enzimática do óleo de soja: efeitos do uso de ultrassom na taxa da reação - Reinehr, Thiago Olinek (2015)
Enzymatic hydrolysis is an important industrial process used to alter oils and fats. Products obtained by this reaction are free fatty acids, monoacylglycerols, diacylglycerols and glycerol, which are used as raw materials for a wide variety of industrial applications. The main limitations of the enzymatic hydrolysis of oils and fats are the immiscibility of the reactants and the inhibition effect caused by increased substrate concentration. The use of ultrasound has emerged as a powerful resource in immiscible substrates processes. The objective of this study was to evaluate different application methods of ultrasonic irradiation on the enzymatic hydrolysis of soybean oil. Kinetics were performed using ultrasound bath, ultrasound probe, and pre-emulsion with and without ultrasound probe ultrasound. The effects of substrate inhibition, surfactant concentration (gum arabic), enzyme load and time preemulsion were also investigated. Mathematical simulations of the process were also performed. The substrate inhibition was evident from the mole fraction of 2.5 % oil in the reaction medium. The surfactant concentration that provided higher rates was 10 mathrmg L-¹. The enzyme loading showed a fraction of saturation at 2.0 % by mass, relative to the mass of water, only for the ultrasound-free reaction, indicating the increase in interfacial area where the substrates were exposed to ultrasound. Even the smallest pre-emulsion times were significant in the initial rate of hydrolysis. Kinetic experiments exposed to ultrasonic irradiation throughout the reaction period showed evidence of significant enzymatic deactivation. The methodology that uses pre-emulsion with probe ultrasound showed better results for the rate of reaction with no evidence of enzyme deactivation. Hydrolysis mathematical simulations were in agreement with the experimental evidence.